COMPARATIVE STUDY ON FREQUENCY DOMAIN FATIGUE ANALYSIS METHODS FOR HALF AXLE OF COMBINE HARVESTER - FU JingJing; WANG ChenSheng; CAI FuYou; NIU WenTie (Jixie qiangdu)
The calculation models of frequency domain fatigue analysis method are various and their accuracy is different. In order to solve the above problems, based on the time domain analysis results of the half axle, the accuracy comparison of frequency domain fatigue analysis methods is carried out. Firstly, the load signals of the half axle under different working conditions are obtained, and the stationarity, Gaussianity and bandwidth were investigated to obtain the basic properties of the load signal. Secondly, the static analysis of the half axle was carried out, and the transfer coefficients of stress and torque at the dangerous node of the walking half axle were obtained. Meanwhile, the stress time histories of the dangerous node of the half axle under various working conditions were obtained. Based on the above stress time histories, the comparative study of fatigue life in time-frequency domain was carried out, in which the average stress and non-Gaussian correction model were introduced to modify the traditional frequency domain method. The results showed that the accuracy of the modified frequency domain method was significantly better than that of the traditional frequency domain method. In the modified frequency domain method, TB2ms+nG and DKms+nG had the highest accuracy. When the above two methods were applied to the stationary load signals, the reliability was high. Nevertheless, when they were applied to the non-stationary load signals, the reliability was low.